1981
DOI: 10.1128/jvi.38.1.383-388.1981
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a protein kinase induced by herpes simplex virus type 1

Abstract: We have isolated a new cyclic AMP-independent protein kinase activity induced in HeLa cells by infection with herpes simplex virus type 1. Induction of the enzyme does not occur in cells treated with cycloheximide at the time of infection, or in cells infected with UV-inactivated herpes simplex virus type 1. The amount of enzyme induced in infected cells is dependent upon the multiplicity of infection. An enzyme with identical properties to that appearing in infected HeLa cells is also induced by herpes simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Interestingly, the earlier investigators of kinases in herpesvirusinfected cultures had observed the phosphorylation of serine or threonine residues rather than tyrosine residues. This finding was supported by more recent studies of alphaherpesviruses which documented diverse serine and threo-nine phosphotransferase activities (1,19,21,25,28). In some instances, the activity resembled that of cellular casein kinase 11 (16).…”
supporting
confidence: 55%
“…Interestingly, the earlier investigators of kinases in herpesvirusinfected cultures had observed the phosphorylation of serine or threonine residues rather than tyrosine residues. This finding was supported by more recent studies of alphaherpesviruses which documented diverse serine and threo-nine phosphotransferase activities (1,19,21,25,28). In some instances, the activity resembled that of cellular casein kinase 11 (16).…”
supporting
confidence: 55%
“…Biochem., in press) and highly purified from cells infected with HSV-1 (27). The substrate specificity and other properties of the enzyme clearly differentiate it from known c'ellular protein kinases (13) and from another activity reported in cells infected with HSV-1 and catalyzing the phosphorylation of the acidic protein phosvitin in vitro (3). Furthermore, the protein kinases induced in cells infected with HSV-1 and PRV could be chromatographically resolved from one another, suggesting, although not proving, that they are viral gene products.…”
mentioning
confidence: 73%
“…A number of workers have proposed that RNA polymerases are partially regulated by a phosphorylationdephosphorylation mechanism (7,8,20,21,37,40). Phosphorylation of proteins also appears to play a role in the control of HSV infections (6,22,30,50). There is a protein kinase activity associated with purified virions (22, 38) and an HSV-specific protein kinase activity which appears within the first hour of infection (6).…”
Section: D)iscussionmentioning
confidence: 99%